PENGARUH BIMBINGAN METODE DISKUSI TERHADAP PERUBAHAN HARGA DIRI NARAPIDANA DI LAPAS KELAS II B KOTA MOJOKERTO - HADI KUSUMA, YUDHA LAGA (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2015)
Experience life in prison was a part of life experience filled with pressure. That was because the prisoner feel the situation was far from loved ones and family and regret that cause negative judgments about themselves that made prisoner experience stress, depression and low self-esteem. The purpose of this study was to analyze the influence of free discussion to increase self-esteem. This study used a quasi-experimental research design with pre-test and post-test control group design. The population in this study were all prisoners in Correctional Institution class II B Mojokerto since November 2014. There were 12 respondents as samples which treated by the free discussion. This treatment was 8 times within a month for each group in this study. Self-esteem were collected by using Coopersmith Self-Esteem Inventory Questionary and then analyzed using two independent samples t-test and paired sample t-test.The results showed that there was no difference between the self-esteem to prisoners before and after free discussion (p value is 0,392). Prisoners Self esteem tend to remain after participating in a free discussion. Motivation for discussion is often low among prisoners. They do not want to interact. It is highly influenced by their self-esteem. Therefore, the management of prisons should consider the use of free speech any given time with a frequency of 1 time per week to provide opportunities for prisoners in order to interact and meet theirsocial needs.Keywords: Prisoner, discussion, self-esteem